Isolated middle ear anomalies: unfamiliar causes of conductive hearing loss: a case series - Vijayendra, Honnurappa; Abhilasha, Somashekhar; Vijayendra, Vinay; Mahajan, Nilesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
In this paper, we highlighted on the various types of isolated congenital middle ear ossicular anomalies we had seen and managed. This is significant as these are rare and go undiagnosed for long period of time. The mainstay of managing these conditions includes proper and timely diagnosis and correction of conducting hearing loss. This was a retrospective case series study done over period of 3 years from July 2016 to June 2019 at a tertiary referral otology centre. The study comprised of 9 patients diagnosed with isolated middle ear anomalies and in total 11 operated ears for the same as two patients underwent bilateral treatment. Each case was handled differently according to the intra operative middle ear findings. We found that in all of our cases the HRCT findings were in correlation with our intra operative findings. All cases had excellent post-operative hearing outcomes. Isolated middle ear deformity even though rare to identity, with recent advancement it is possible to diagnose and treat it on time and hence reduce the disability experienced by the patient. Whatever the type of abnormalities, most of them could be corrected with appropriate ossicular reconstruction by preserving the normal existing anatomy and bypassing the anomalous part.